Text Complexity in Digital Language Learning: Analyzing the Readability and Lexical Density of Duolingo's Guidance Textbook - Azzahra, Sekar; Silaban, Jelly Prima Krisnawati; Sinar, Tengku Silvana (Universitas Pamulang, 2025)
This paper establishes the lexical density and readability levels of the Duolingo guidance textbook, with the view of establishing further the accessibility levels that the textbook has for use in language learning by users. Qualitative content analysis was conducted on 10 segments of the guidance text; lexical density was determined through content word proportions analyzed and readability by the Flesch Reading Ease formula. The results ranged between 47.6% and 56.1% for lexical density, while for nouns, just one word class, the most frequent class of words for all observed segments was 24.9-32.5%. Scores for readability ranged from 53.21 to 85.2. For example,